Feeding Selectivity of Ruditapes philippinarum on Phytoplankton - Yin Liu; Lun Song; Guangjun Song; Jinhao Wu; Kun Wang; Zhaohui Wang; Suxuan Liu (Fishes, 2022)
A monthly survey of the feeding selectivity of Ruditapes philippinarum in the Yalu River Estuary in 2020–2021 was conducted using high-throughput sequencing identification and visual grading technology. The results showed that the most-dominant species in the water of the shellfish culture area and in the stomachs of R. philippinarum was Karlodinium veneficum in those years. The selectivity index (E) indicated that R. philippinarum avoided consuming Bacillariophyta, Chrysophyta and Cryptophyta throughout the year and preferentially consumed Dinophyta and Chlorophyta. In 2020, the annual average biomass of Dinophyta, Bacillariophyta, Chlorophyta, Dictyochophyta, Cryptophyta and Chrysophyta in the stomach contents of R. philippinarum was 54:14:16:1:10:4; it was 41:12:28:0:1:17 in 2021. The annual average biomass ratio of picophytoplankton, nanophytoplankton and microphytoplankton in the stomachs of R. philippinarum was 13:48:39 in 2020; it was 14:66:20 in 2021. R. philippinarum actively fed on nanophytoplankton and avoided picophytoplankton. Among the phytoplankton of different sizes and groups that R. philippinarum prefer to feed, chemical oxygen demand (COD) and organic phosphorus (DOP) have a significant negative effect on the nanophytoplankton community, pH has a positive effect on the Dictyochophyta community and COD and the inorganic nitrogen to phosphorus ratio (DI-N/P) have a significant positive effect on the Chlorophyta community.